Hubungan Pengetahuan dengan Tingkat Kecemasan Remaja Putri Usia 10-13 Tahun dalam Menghadapi Menarche - Puspitasari, Betristasia; Dyah Ika Krisnawati (STIKES Ngesti Waluyo, 2022)
Menarche, which is often known as the beginning of maturity in girls, is usually characterized by the start of the first menstruation. Normally, the menstrual cycle proceeds regularly. Teenager who are never been informed about menstruation and reproductive health could experience anxiety when facing menarche. Providing information early is one way to reduce anxiety and increase the knowledge of young women in facing menarche. The purpose of this study was to determine the correlation between knowledge and the anxiety level of girls aged 10-13 in facing menarche in RW 02 Sidomulyo Village, Semen District, Kediri Regency. The research used a correlation design with a cross-sectional approach. The population of this study was young women aged 10-13 years in RW 02 Sidomulyo Village, Semen District, Kediri Regency, which amounted to 30 respondents. The sampling technique in this study was total sampling. The types of instruments used in this study were knowledge questionnaires and HARS scale questionnaires. The data then analyzed using the Spearman Rho test. The study result showed that among 30 respondents studied, most of the respondents have enough knowledge (19 respondents; 63.3%); while about the anxiety level, most of them have mild anxiety (12 respondents; 40%). The results of the Spearman Rho test with α=0.05 obtained the p-value=0.031 (< 0.05), it is indicated that there is a correlation between knowledge and the level of anxiety of young women aged 10-13 in facing menarche. Based on the results of the study, information about menstruation should be improved by counseling, so that young women can face menarche without excessive anxiety.